Knowledge spillovers in the process of formation of the economic clusters - Elina BENEA-POPUȘOI; Ecaterina RUSU (Eastern European Journal of Regional Studies, 2018)
Knowledge creation and innovation represent the result of an interactive process of collaboration between various actors that come together to solve the problems they face. However, due to the complexity of the knowledge dimension, the creation and exchange of information don’t occur automatically, it requires a special environment that could facilitate these processes. Spatial clustering of economic activity proved to be an efficient way to organize interactive learning processes, offering the perfect infrastructure for fostering that collaboration between its participants, from which all of them can grasp advantages in terms of acquiring new technical, organizational, commercial or intellectual competences.